Administering enteral tube medications – room for improvement?. Issue 4 (29th June 2012) - Williams, Teresa
Abstract : Commentary on: Phillips NM Endacott R . Medication administration via enteral tubes: a survey of nurses' practices. J Adv Nurs 2011 ;67 :2586 –92 .